2014
DOI: 10.1007/978-3-319-06569-4_26
|View full text |Cite
|
Sign up to set email alerts
|

Application of Sigmoid Models for Growth Investigations of Forest Trees

Abstract: Abstract. Radial growth of the trees and its relationships with other factors is one of the most important research areas of forestry for a long time. For measuring intra-annual growth there are several widely used methods: one of them is measuring the girth of trees regularly, preferably on weekly basis. However, the weekly measured growth data may have bias due to the actual precipitation, temperature or other environmental conditions. This bias can be reduced and using adequate growth functions the discrete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
9
0
1
Order By: Relevance
“…One cutblock had very low P. tremuloides counts on the seismic lines, and so this cutblock was excluded from the P. tremuloides model. While sigmoidal functions are often used for modeling tree growth (Pödör et al, 2014), plots of our data showed an approximately linear relationship between tree height and age over the first fifteen years of growth. A separate linear mixed effect model (LMM) was used to model each species (P. tremuloides and P. controta) using the nlme package (Pinheiro et al, 2022) with height as the response variable and both age (covariate) and location specified as fixed effects while individual Tree ID nested within 12 Transect ID within Cutblock ID were included as random effects.…”
Section: Discussionmentioning
confidence: 63%
“…One cutblock had very low P. tremuloides counts on the seismic lines, and so this cutblock was excluded from the P. tremuloides model. While sigmoidal functions are often used for modeling tree growth (Pödör et al, 2014), plots of our data showed an approximately linear relationship between tree height and age over the first fifteen years of growth. A separate linear mixed effect model (LMM) was used to model each species (P. tremuloides and P. controta) using the nlme package (Pinheiro et al, 2022) with height as the response variable and both age (covariate) and location specified as fixed effects while individual Tree ID nested within 12 Transect ID within Cutblock ID were included as random effects.…”
Section: Discussionmentioning
confidence: 63%
“…Regarding the differences between the applicable sigmoid functions, based on goodness of fit values and general interpretability, the Gompertz, Weibull, and general logistic (not shown in DevX) models can certainly almost equally be used to characterize seasonal growth patterns of tree ring formation in temperate environments (Pödör et al, 2014). For our case study, the Gompertz derived phenology consistently delivered estimates closer to the histological evidence.…”
Section: Case Study-xylem Phenology Of Central European Temperate Trementioning
confidence: 74%
“…These have great explanatory power and are commonly applied in forest science. In forestry, they have been widely applied to describe the growth of dendrometric variables of species with timber potential (PÖDÖR et al, 2014;VENDRUSCOLO et al, 2017;SILVA et al, 2018) as well as to describe hypsometric relations (ALVES et al, 2017;ANDRADE, 2017;MACHADO et al, 2019).…”
Section: Growth Modelsmentioning
confidence: 99%